Localized contact urticaria due to epoxy resin-based endodontic sealer - Afzal Ali; Meltem Sümbüllü; Aasima İshaq; Hakan Arslan (Wolters Kluwer Medknow Publications, 2022)
This case report aimed to report the localized contact Urticaria with epoxy resin-based root canal sealer (AH Plus). Dental materials usually contain chemical that may cause potential allergic reactions to the clinicians as well as patients. Occupational disease in form of contact dermatitis may occur to the dentists. An adolescent postgraduate student in the department of conservative dentistry and endodontics, with an ASA physical status I encountered itching, erythema, and swelling of her left-hand skin with the first-time use of AH Plus sealer in her career. A diagnosis of Contact Urticaria was established by the dermatologist upon examination. Topical steroids and antihistamine drugs were advised to the endodontic postgraduate and within a week the symptoms were resolved. The case report focuses attention on handling of epoxy resin-based root canal sealer. The dentists should exercise care and follow manufacturer's instructions while handling the dental materials.